Evaluation of Antioxidant Properties of Elaeagnus angustifolia Flowers - Caliskan, E.; Elmastas, M.; Gokce, I. (Asian Journal of Chemistry, 2010)
In the present work, ethanol extract of oleaster was evaluated by employing various in vitro antioxidant assay such as total antioxidant activity determination by ferric thiocyanate, total reducing ability determination by Fe3+-Fe2+ transformation method, 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH•) scavenging, superoxide anion radical scavenging by riboflavin/ methionine/illuminate system. Ethanol extract of oleaster inhibited lipid peroxidation of linoleic acid emulsion, scavenging free radical (DPPH) and superoxide anion radical. The obtained results about ethanol extract of oleaster was compared with the standard antioxidant compounds such as butylated hydroxyanisole, butylated hydroxytoluene and α-tocopherol at the same conditions.